Refractory high entropy superalloys (RSAs) - Miracle, Daniel B.; Tsai, Ming-Hung; Senkov, Oleg N.; Soni, Vishal; Banerjee, Rajarshi (Scripta materialia, 2020)
Complex, concentrated alloys (CCAs) containing refractory principal elements and Al can have microstructures with disordered body-centered cubic (BCC) and ordered B2 phases that are remarkably similar to superalloys. The simple idea of copying superalloy microstructures in these BCC-based refractory alloys introduces a set of audacious challenges. BCC metals and B2 compounds are often brittle at room temperature; the B2 phase is unstable in refractory-Al binaries and reasons for its stability in higher-order systems are a mystery; and many refractory metals and alloys display catastrophic oxidation. Here we discuss opportunities and challenges to develop RSAs as new high temperature structural materials. [Display omitted]